Konkordat podpisany ze Stolicą Apostolską w 1993 r. jako źródło prawa w Rzeczypospolitej Polskiej - Banaszkiewicz, Adam (Wydawnictwo Naukowe UAM, 2015)
A concordat between the Holy See and a secular state is a document regulating the relationships between the two subjects. This article discusses the Concordat entered into by the Republic of Poland and the Holy See in 1993 (in force as of 1998) as one of the sources of law in Poland. First, the issue of international agreements (treaties) is described with particular attention given to the speciﬁcs of a concordat as an international agreement. Next, the term ‘concordat’ is deﬁned and its evolution over the centuries presented as a consequence of the change in the legal status of the Vatican and the Holy See, in result of which concordats became agreements between sovereign subjects of international law. Certain concordat theories have been subsequently analysed, with particular focus put on the binding theory of an international convention. The second part of the article focuses on the history of the institution of a con cordat (including the circumstances accompanying its conclusion such as the requirement of compliance with e.g. the laws in Poland), its purpose, character and content. The main goal of the considerations was to analyse the principles upon which the relationships between the Polish state and the Catholic church have been based. Those relationships constituted the essence of the reasons for entering into the Concordat by the Polish state. Although the concluded Concordat maintains and provides for all essential elements characterising a secular state, a potential conﬂict of its provisions and the provisions of Polish law has been signalled. The article ends with an overview of the realisation of the goals foreseen in the Concordat during almost twenty years of its operation in Poland.
Concordat entered into with the Holy See in 1993 as a source of law of the Republic of Poland
Keywords: Concordat; international agreement; treaty; Holy See; Catholic Church; freedom of religion